Storage Stability Study of Sesame (Sesamum Indicum) Seed-Based Salad Cream - Okwunakwe, Ada Florence; Anhwange, Benjamin Asen; Adie, Peter Agorye; Ariahu, Charles Chukwuma (Indonesian Food and Nutrition Progress, 2025)
The quality and storage stability of sesame seed-based salad cream containing varied quantities of acetic acid were compared with a renowned commercial salad cream. Variations in pH, peroxide value, total titratable acidity, free fatty acid, thiobarbituric acid, viscosity, and microbial parameters of samples stored in an airtight container for 6 months at 20 °C were determined using standard methods. Storage stability parameters (pH, peroxide oxide, free fatty acid, total titratable acidity, thiobarbituric acid, viscosity, and microbial analysis) had significant differences (P < 0.05) during six months of storage. The samples were chemically stable, but the viscosity of the samples decreased below the Standards Organization of Nigeria specification at week 24. Sample 462 and sample 795 were not microbiologically stable. The decrease in total plate count and the inhibitory effect of acetic acid on microorganisms were observed to be proportional to the concentration of acetic acid.